Math, asked by omkarbasotia, 4 months ago

Prove that: (1 + sin A - cos A)/(1 + sin A + cos A) = sqrt((1 - cos A)/(1 + cos A))​

Answers

Answered by mathdude500
44

Identities Used :-

 \boxed{ \red{ \bf \: \dfrac{sinx}{cosx}  = tanx}}

 \boxed{ \red{ \bf \: \dfrac{1}{cosx}  = secx}}

 \boxed{ \red{ \bf \: \dfrac{1}{sinx}  = cosecx}}

\boxed{ \red{ \bf \:  {sin}^{2} x +  {cos}^{2} x = 1}}

\boxed{ \red{ \bf \:  {cosec}^{2} x -  {cot}^{2} x = 1}}

\large\underline{\sf{Solution-}}

Consider,

\rm :\longmapsto\:\dfrac{1 + sinA - cosA}{1 + sinA + cosA}

On dividing numerator and denominator by sinA, we get

\rm :\longmapsto\:  \: =  \:  \:\dfrac{\dfrac{1}{sinA}  + \dfrac{sinA}{sinA}  - \dfrac{cosA}{sinA} }{\dfrac{1}{sinA}  + \dfrac{sinA}{sinA}  + \dfrac{cosA}{sinA} }

\rm :\longmapsto\:  \: =  \:  \:\dfrac{cosecA + 1 - cotA}{cosecA +1 +  cotA}

\rm :\longmapsto\:  \: =  \:  \:\dfrac{cosecA  - cotA  + ( {cosec}^{2}A -  {cot}^{2}A)}{cosecA + cotA + 1}

\rm :\longmapsto\:  \: =  \:  \:\dfrac{(cosecA  - cotA) + (cosecA + cotA)({cosec}A -  {cot}A)}{cosecA + cotA + 1}

\rm :\longmapsto\:  \: =  \:  \:\dfrac{(cosecA  - cotA)(cosecA + cotA + 1)}{cosecA + cotA + 1}

\rm :\longmapsto\:  \: =  \:  \:cosecA - cotA

\rm :\longmapsto\:  \: =  \:  \: \sqrt{ {(cosecA - cotA)}^{2} }

\rm :\longmapsto\:  \: =  \:  \: \sqrt{ {\bigg(\dfrac{1}{sinA}  - \dfrac{cosA}{sinA}  \bigg) }^{2} }

\rm :\longmapsto\:  \: =  \:  \: \sqrt{ {\bigg(\dfrac{1 - cosA}{sinA}\bigg) }^{2} }

\rm :\longmapsto\:  \: =  \:  \: \sqrt{\dfrac{ {(1 - cosA)}^{2} }{ {sin}^{2}A } }

\rm :\longmapsto\:  \: =  \:  \: \sqrt{\dfrac{ {(1 - cosA)}^{2} }{1 -  {cos}^{2}A } }

\rm :\longmapsto\:  \: =  \:  \: \sqrt{\dfrac{ {(1 - cosA)}^{2} }{(1 -  {cos}A)(1 + cosA) }}

\rm :\longmapsto\:  \: =  \:  \: \sqrt{\dfrac{ (1 - cosA) }{(1 + cosA) }}

\rm :\longmapsto\:  \: =  \:  \: \sqrt{\dfrac{ 1 - cosA}{1 + cosA}}

{\boxed{\boxed{\bf{Hence, Proved}}}}

Additional Information:-

Relationship between sides and T ratios

sin θ = Opposite Side/Hypotenuse

cos θ = Adjacent Side/Hypotenuse

tan θ = Opposite Side/Adjacent Side

sec θ = Hypotenuse/Adjacent Side

cosec θ = Hypotenuse/Opposite Side

cot θ = Adjacent Side/Opposite Side

Reciprocal Identities

cosec θ = 1/sin θ

sec θ = 1/cos θ

cot θ = 1/tan θ

sin θ = 1/cosec θ

cos θ = 1/sec θ

tan θ = 1/cot θ

Co-function Identities

sin (90°−x) = cos x

cos (90°−x) = sin x

tan (90°−x) = cot x

cot (90°−x) = tan x

sec (90°−x) = cosec x

cosec (90°−x) = sec x

Fundamental Trigonometric Identities

sin²θ + cos²θ = 1

sec²θ - tan²θ = 1

cosec²θ - cot²θ = 1

Similar questions